2015
DOI: 10.4209/aaqr.2014.12.0332
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Aerosols in Pakistan: Contributions of Domestic Anthropogenic Emissions and Transboundary Transport

Abstract: Air pollution has become a serious challenge for developing countries like Pakistan. Very scarce information is available regarding pollution levels in this geographic region. This study presents the first modelling work to simulate the spatial distribution and temporal variation of aerosol concentrations over Pakistan by using the Weather Research and Forecasting Model coupled with chemistry (WRF-Chem). Simulated aerosols species include sulfate, nitrate, ammonium, organic carbon, black carbon, and PM 2.5 (pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…It can be clearly identified that AOD in the UIP region is contributed to by NO 2 and SO 2 emission sources (precursor of nitrates and sulfate aerosols) while the LIP region is dominated by CO emissions-a good tracer of fire activities and for the presence of both organic and elemental carbon. Our findings about major aerosol sources are in agreement with source apportionment of the particulate matter presented in previous studies [37][38][39][40][41]. High aerosol levels are influencing climate and the hydrological cycle due to dimming and atmospheric warming [76,77].…”
Section: Major Sources Of Aerosolssupporting
confidence: 81%
See 1 more Smart Citation
“…It can be clearly identified that AOD in the UIP region is contributed to by NO 2 and SO 2 emission sources (precursor of nitrates and sulfate aerosols) while the LIP region is dominated by CO emissions-a good tracer of fire activities and for the presence of both organic and elemental carbon. Our findings about major aerosol sources are in agreement with source apportionment of the particulate matter presented in previous studies [37][38][39][40][41]. High aerosol levels are influencing climate and the hydrological cycle due to dimming and atmospheric warming [76,77].…”
Section: Major Sources Of Aerosolssupporting
confidence: 81%
“…Air masses propagated over the densely populated and industrial regions of Uttarakhand, western parts of Uttar Pradesh, Haryana, New Delhi and the Punjab before entering Pakistan. Almost similar transport patterns were observed for both days, which indicates transboundary air pollution as an important factor contributing to high aerosol loading observed over the city of Lahore, Pakistan [39,40]. Moreover, CALIPSO overpasses over the Pakistan were used to further identify the aerosol layer, types and clouds by using the vertical feature mask on both days.…”
Section: Hysplit Back Trajectory Analysismentioning
confidence: 98%
“…By employing the WRF‐Chem, Shahid et al . [] indicated that the lowest PM 2.5 concentration in July in Pakistan may be attributed to the largest summer rainfall associated with the SASM, and that winds over South Asia are the major meteorological factor that determines the transboundary aerosol transport to northeastern Pakistan.…”
Section: Impact Of the Asian Monsoon On Aerosolsmentioning
confidence: 99%
“…In comparison to the past models (such as MM5, Model 3, and SAQM), WRF produces a friendly environment for massively parallel computation by the improved characteristics of non-hydrostatic air flow fields and provides various choices for physical parameterizations (Jiang et al, 2008;Kumar et al, 2012;Lo and Huang, 2012;Huang et al, 2013;Shahid et al, 2015). WRF is good for investigating regional-scale air flow field program analysis (Borge et al, 2008;Peckham et al, 2012).…”
Section: Wrf Model Operation and Domain Settingmentioning
confidence: 99%